Reflections on the Performance of the Principles of Labor Law - Neves Mujica, Javier (1987)
This text examines the impact of labor law principles in specific contexts, using as a case study the suspension of daylight saving time in Peru during 1986 and 1987. According to the facts of the case, this schedule, which reduced the working day for state and public administration workers, was restored to 8 hours by emergency decrees. Based on this, the validity of such decrees is questioned due to the non-compliance with the requirements of urgent and extraordinary necessity, as well as the violation of the workers' acquired rights. In this context, the author analyzes two possible interpretations of Article 44 of the Constitution: one of a progressive nature, which prohibits the retrogression in the protection of labor rights, and another that allows the extension of the working day within the 8-hour limit. By virtue of this, a balanced perspective is proposed that guarantees respect for acquired rights and prioritizes the application of the principle of the most favorable norm. Finally, it should be noted that the amparo actions filed against these decrees were successful, establishing a significant precedent in the labor law field.